Development and Pilot Study of a Pediatric Screening for Feeding and Swallowing Disorders in Infants and Children: The Pediatric Screening-Priority Evaluation Dysphagia (PS-PED) - Antonella Cerchiari; Marco Tofani; Carolina Giordani; Silvia Franceschetti; Eleonora Capuano; Francesca Pizza; Gessica Della Bella; Massimiliano Raponi; Giorgia Biondo (MDPI AG, 2023)
Feeding and swallowing disorders (FSD) are common during childhood, with a prevalence of 85% in children with neurodevelopmental disorders. A comprehensive screening is essential to identify FSD and improve health outcomes in a clinical setting. This study aims to develop a new Pediatric Screening tool capable of identifying FSD. This screening tool was developed in three steps: selecting variables based on clinical experience, searching the literature and finding agreement between experts with a two-round Delphi study. This process, which reached 97% of agreement between experts, led to the development of the Pediatric Screening-Priority Evaluation Dysphagia (PS-PED). PS-PED comprises 14 items divided into three main domains: clinical history, health status and feeding condition. We also carried out a pilot test for measuring internal consistency, as measured with Cronbach Coefficient alpha. Concurrent validity, as measured with Pearson correlation coefficient, was tested using a videofluoroscopy swallow study (VFSS) classified with the Penetration Aspiration Scale (PAS). The pilot test was conducted on 59 children with different health conditions. Our findings showed good internal consistency (alpha = 0.731), and a strong linear correlation with PAS (Pearson 0.824). Furthermore, comparing PS-PED and PAS scores, we find preliminary strong discriminant validity to identify children with FSD (p < 0.01). Our results provide evidence on using the 14-item PS-PED as a screening tool for FSD in a clinical sample of children with heterogeneous disease.